Pengembangan Multimedia Interaktif berbasis Problem Based Learning untuk Meningkatkan Hasil Belajar IPAS - Husna Maulida Adhana; Aldina Eka Andriani (Jurnal Penelitian Pendidikan IPA, 2024)
This research is an R&D (Research and Development) study with the Borg and Gall model. This research is motivated by the fact that teachers have not been optimal in using technology-based learning media and innovative learning models. This causes the low learning outcomes of grade V students on the material of the human digestive system. This research aims to develop media design, test the feasibility, and test the effectiveness of interactive multimedia based on problem-based learning. The techniques used in data collection are tests and non-tests (observation, interviews, questionnaires, and documentation). The results showed that (1) interactive multimedia was developed using the Canva application with components including cover, main menu, instructions, problem-based learning-based material, games, evaluation, and developer profile; (2) product feasibility from media experts 93.75%, material experts 92.5%, student responses 97.27%, and teacher responses 98.75% with very feasible criteria; (3) effectiveness seen from the increase in learning outcomes of 19.4948 and sig. (2-tailed) value of 0.000 which shows there is a significant difference in students before and after using interactive multimedia. The N-Gain test obtained was 0.4911 which showed medium criteria. The conclusion of this study states that interactive multimedia based on problem-based learning has been successfully developed, feasible, and effective in improving the learning outcomes of human digestive system IPAS of fifth-grade students of SD N 1 Ngadirejo Temanggung.